Portuguese consensus document for the management of alpha-1-antitrypsin deficiency - Lopes, A. (2020)
Alpha-1-antitrypsin deficiency (AATD) is a genetic autosomal codominant disorder caused by mutations in SERPINA1 gene. It is one of the most prevalent genetic disorders, although it remains underdiagnosed. Whereas at international level there are several areas of consensus on this disorder, in Portugal, inter-hospital heterogeneity in clinical practice and resources available have been adding difficulties in reaching a diagnosis and in making therapeutic decisions in this group of patients. This raised a need to draft a document expressing a national consensus for AATD. To this end, a group of experts in this field was created within the Portuguese Pulmonology Society - Study group on AATD, in order to elaborate the current manuscript. The authors reviewed the existing literature and provide here general guidance and extensive recommendations for the diagnosis and management of AATD that can be adopted by Portuguese clinicians from different areas of Medicine. This article is part of a supplement entitled "Portuguese consensus document for the management of alpha-1-antitrypsin deficiency" which is sponsored by Sociedade Portuguesa de Pneumologia.